Hypervideo : interface design for collaborative documentaries : exegesis submitted in partial fulfilment of the Master of Design at Massey University, Wellington, New Zealand - Turnidge, Tim (Massey University, 2014)
Hypervideo is developed in response to the collaborative mobile-mentary 24 Frames 24 Hours. Through practice-led research an online interface is designed that creates a dynamic remix of user submitted and workshop generated videos. By means of leveraging contemporary web technologies such as APIs, metadata and video databases the interface presents an interactive documentary as a way of exploring innovative possibilities of web 2.0. The interface facilitates a unique viewing experience, which encourages new ways of experiencing and inspires the creation of mobile movies. This interactive documentary film form is influenced by Soft Cinema (Manovich, 2002) and the Korsakow system (Thalhofer, 2000). The interface is developed through an iterative design process in response to the emerging significance of metadata in online viewing formats and the vertical/horizontal video design problem.
Keywords: User interfaces (Computer systems); Documentary films; Production and direction; Interface design; Database cinema; Interactive documentary; Metadata; Web APIs; Mobile media